Genetic variability in apomictic mangosteen (Garcinia mangostana) and its close relatives (Garcinia spp.) based on ISSR markers - SOBIR SOBIR; ROEDHY POERWANTO; EDY SANTOSA; SOALOON SINAGA; ELINA MANSYAH (Biodiversitas Journal of Biological Diversity, 2011)
Sobir, Poerwanto R, Santosa E, Sinaga S, Mansyah E (2011) Genetic variability in apomictic mangosteen (Garcinia mangostana) and its close relatives (Garcinia spp.) based on ISSR markers. Biodiversitas 12: 59-63. In order to reveal phylogenetic relationship of mangosteen and several close relatives (Garcinia spp.), we employed seven ISSR dinucleotide primer systems on eleven close relatives of mangosteen and 28 mangosteen accessions from four islands in Indonesia (Sumatra, Java, Kalimantan and Lombok). ISSR analysissuccessfully amplified 43 bands on average 6.1 fragments for each primer system, and these all fragments were polymorphic. Seven close relatives of mangosteen were separated with mangosteen accessions at 0.22 level of dissimilarity, while other four including G. malaccensis, were clustered with mangosteen accessions, this results supported proposal that G. malaccensis was allopolyploid derivative of mangosteen. Clustering pattern among mangosteen accessions, however, not represented their origin, indicated that distribution of the accessions was not linked to their genetic properties.